Policy-Driven Development and the Strategic Initiative of One-Million Enrollment Expansion in China's Higher Vocational Education. (March 2020) - Fan, Xiaoxian
Purpose: This article explores the relationship between governmental policy and the development of higher vocational education in China. Design/Approach/Methods: The article begins with a textual analysis of dozens of policy documents on higher vocational education issued by the Chinese government since 1999. Findings: The article argues that the development of higher vocational education in China has been largely policy-driven. This development can be divided into four stages: scale development, quality improvement, capacity building, and systemwide enhancement. The transition between each of these developmental stages was marked by new policy initiatives undertaken by the Chinese government. Originality/Value: The government's recent efforts to expand higher vocational education enrollment by one million students have significant implications for China's higher vocational education. Additionally, the proposed "1 + X" model—which attaches equal importance to academic education and skill training—may represent the beginning of a new stage in the development of higher vocational education in China.